PERAN AKTOR POLITIK DALAM KEBIJAKAN PEMBATASAN WISATAWAN UNTUK MENGATASI OVER KAPASITAS: STUDI KASUS PANTAI KUTA BALI - Richard Albert Seto; Tedi Ervianto; Piers Andreas Noak (PT. Saha Kreasi Indonesia, 2025)
This study explores the dynamics of actors and institutions in the implementation of tourist restriction policies in Bali, particularly in the Kuta area of Badung Regency. The policy emerged as a response to the negative impacts of mass tourism, such as environmental degradation and the erosion of local culture. Using a qualitative approach, data were collected through in-depth interviews, field observations, and document analysis. The findings reveal that the implementation of the restriction policy involves complex interactions among various actors, including local government, business owners, local communities, and tourists. Differences in vision and interests among these actors often lead to resistance, policy conflict, and political interference. Applying the neo-institutionalist perspective, this research highlights how formal and informal institutions shape actor behavior and policy outcomes. The tension between economic interests and sustainability presents a major challenge to the effectiveness of the policy. This study recommends the formulation of more inclusive and participatory tourism policies, as well as institutional strengthening to mediate stakeholder interests toward sustainable tourism governance.